Managers and Productivity Differences - Nezih Guner; Andrii Parkhomenko; Gustavo Ventura (Institute for the Study of Labor (IZA), 2015)
We document that for a group of high-income countries (i) mean earnings of managers tend to grow faster than for non managers over the life cycle; (ii) the earnings growth of managers relative to non managers over the life cycle is positively correlated with output per worker. We interpret this evidence through the lens of an equilibrium life-cycle, span-of-control model where managers invest in their skills. We parameterize this model with U.S. observations on managerial earnings, the size-distribution of plants and macroeconomic aggregates. We then quantify the relative importance of exogenous productivity differences, and the size-dependent distortions emphasized in the misallocation literature. Our findings indicate that such distortions are critical to generate the observed differences in the growth of relative managerial earnings across countries. Thus, observations on the relative earnings growth of managers become natural targets to discipline the level of distortions. Distortions that halve the growth of relative managerial earnings (a move from the U.S. to Italy in our data), lead to a reduction in managerial quality of 27% and to a reduction in output of about 7% – more than half of the observed gap between the U.S. and Italy. We find that cross-country variation in distortions accounts for about 42% of the cross-country variation in output per worker gap with the U.S.
Keywords: E23; E24; J24; M11; O43; O47; 330; managers; management practices; distortions; size; skill investments; productivity differences